Urinary Neutrophil Gelatinase Associated Lipocalins (NGALs) predict acute kidney injury post liver transplant. Issue 4 (April 2019) - Robertson, Francis P.; Yeung, Arthur C.; Male, Victoria; Rahman, Suehana; Mallett, Susan; Fuller, Barry J.; Davidson, Brian R.
Abstract: Background: Acute Kidney Injury, a common complication of liver transplant, is associated with a significant increase in the risk of morbidity, mortality and graft loss. Current diagnostic criteria leaves a delay in diagnosis allowing further potential irreversible damage. Early biomarkers of renal injury are of clinical importance and Neutrophil Gelatinase Associated Lipocalins (NGALs) and Syndecan-1 were investigated. Methods: AKI was defined according to the Acute Kidney Injury Network criteria. Urine and blood samples were collected pre-operatively, immediately post-op and 24 h post reperfusion to allow measurement of NGAL and Syndecan-1 levels. Results: 13 of 27 patients developed an AKI. Patients who developed AKI had significantly higher peak transaminases. Urinary NGAL, plasma NGAL and Syndecan-1 levels were significantly elevated in all patients post reperfusion. Urinary NGAL levels immediately post-op were significantly higher in patients who developed an AKI than those that didn't [1319 ng/ml vs 46.56 ng/ml, p ≤ 0.001]. ROC curves were performed and urinary NGAL levels immediately post-op were an excellent biomarker for AKI with an area under the curve of 0.948 (0.847–1.00). Conclusions: Urinary NGAL levels measured immediately post-op accurately predict the development of AKI and their incorporation into clinical practise could allow early protocols to be developed to treat post transplant AKI.